login
A078338
Let u(1)=u(2)=u(3)=1 and u(n)=(-1)^n*sign(u(n-1)-u(n-2))*u(n-3), then a(n)=sum(k=1,n,u(k)).
0
1, 2, 3, 3, 4, 5, 5, 4, 5, 5, 4, 3, 3, 2, 1, 1, 2, 1, 1, 2, 3, 3, 4, 5, 5, 4, 5, 5, 4, 3, 3, 2, 1, 1, 2, 1, 1, 2, 3, 3, 4, 5, 5, 4, 5, 5, 4, 3, 3, 2, 1, 1, 2, 1, 1, 2, 3, 3, 4, 5, 5, 4, 5, 5, 4, 3, 3, 2, 1, 1, 2, 1, 1, 2, 3, 3, 4, 5, 5, 4, 5, 5, 4, 3, 3, 2, 1, 1, 2, 1, 1, 2, 3, 3, 4, 5, 5, 4, 5, 5, 4, 3, 3, 2, 1
OFFSET
1,2
FORMULA
Periodic with period 18.
MATHEMATICA
LinearRecurrence[{1, 0, 0, 0, 0, 0, 0, 0, -1, 1}, {1, 2, 3, 3, 4, 5, 5, 4, 5, 5}, 105] (* Ray Chandler, Aug 27 2015 *)
CROSSREFS
Sequence in context: A240153 A241435 A349320 * A338587 A338580 A278149
KEYWORD
nonn
AUTHOR
Benoit Cloitre, Nov 21 2002
STATUS
approved